A considerable proportion of CRF01_AE strains in China originated from circulating intrasubtype recombinant forms (CIRF). Issue 1 (December 2015) - Jia, Lei; Gui, Tao; Li, Lin; Liu, Siyang; Li, Hanping; Bao, Zuoyi; Wang, Xiaolin; Zhuang, Daomin; Li, Tianyi; Han, Jingwan; Liu, Yongjian; Li, Jingyun
Abstract Background In this study, the prevalence of HIV-1 CRF01_AE intrasubtype recombinants in China is estimated and their contributions to the epidemic are explored. Methods Available HIV-1 complete genomes of CRF01_AE were retrieved from the HIV database. The two alignments were evaluated with RDP3. Recombinants were defined as cases in which the recombination signal was supported by at least 3 methods withP -values of ≤0.05 after Bonferroni correction for multiple comparisons implemented in RDP3. Phylogenetic analysis was performed to further investigate the role of intrasubtype recombinants in epidemics. Results Here, 124 out of the 339 sequences from around the world (36.6 %) showed significant evidence of recombination. Here, 84 of these recombinants were from China, accounting for 54.9 % of local total sequences (84 out of 153). The results indicated non-negligible levels of intrasubtype recombination. Subsequent phylogenetic analysis indicated that a considerable proportion of CRF01_AE strains in China originated from circulating intrasubtype recombinant forms. Three large, well-supported intrasubtype recombinants clusters were identified here. Through a survey of risk factors and sampling cities and provinces, cluster I and cluster II were found to be prevalent primarily among men who have sex with men in major northern cities. Cluster III was prevalent among heterosexuals and intravenous drug users in southern and southwestern provinces. Conclusions The current work highlighted the remarkable prevalence of intrasubtype recombination within the CRF01_AE epidemic and emphasized the value of intrasubtype recombinants, which came to circulate in the same manner as intersubtype recombinants.